Anti-viral and in-vitro free radical scavenging activity of leaves of Rubia cordifolia - Sarju N. Prajapati; Kokila A. Parmar (International Journal of Phytomedicine, 2011)
The aim of this research was to develop the pharmacognostical parameters and phytochemical screening along with histological studies and the leaf powder of Rubia cordifolia. The dried leaves of Rubia cordifolia. (Family: Rubiaceae) were subjected to standardization by following pharmacognostical and phytochemical screening methods. Rubia cordifolia was investigated for preliminary phytochemical analysis and characterization by various instrumental techniques. Methanolic extracts of Rubia cordifolia leaves was very good antibacterial activity and also minimum inhibitory concentrating of different virus using HEL cell cultures, HeLa cell cultures and Vero cell cultures but MIC of Herpes simplex - 1 and 2, vaccinia virus, vesicular stomatitis and Herpes simplex- 1 (TK ACVI) were observed very good antiviral activity of Rubia cordifolia leaves DMSO extracts has good minimum cytotoxic concentration activity and also screening for various pharmaceuticals activities. Such as anti oxidant and microbial activities.